Effects of Manure Removal Frequencies and Deodorants on Ammonia and GHG Concentrations in Livestock House - Xia Zhang; Jian Li; Le Shao; Hailin Huan; Feng Qin; Pin Zhai; Jie Yang; Xiaoqing Pan (Atmosphere, 2022)
In order to mitigate the concentration of NH3 and greenhouse gases (GHGs: CO2, N2O, CH4) in livestock houses, two experiments, one determining the ideal manure removal frequency by cleaning the feces from a livestock house once, twice, three, and four times a day, and one in which microbial deodorant and VenaZn deodorant were sprayed, were conducted in a rabbit breeding house. The NH3, CO2, N2O, and CH4 concentrations were monitored continuously with an Innova 1512 photoacoustic gas monitor during the experiments. The results were as follows: the manure removal frequency had a significant impact on the average concentrations of NH3, CO2, and CH4 in the rabbit house. Cleaning the feces in the rabbit breeding house two to three times a day significantly reduced the NH3 concentration, and, on the contrary, cleaning the feces four times a day increased the NH3 concentration in rabbit house; increasing the manure removal frequency significantly reduced the concentrations of CO2 and CH4 in the rabbit house. Considering the average concentrations of NH3, CO2, N2O, and CH4 in the rabbit house and economic cost, it was better to remove feces twice a day. The average NH3 and CO2 concentration declined significantly within 3 days in the summer and winter; the N2O concentration declined within 3 days in the summer but did not decline in the winter; and there was no effect on the CH4 concentration in the summer and in the winter after spraying the rabbit house with microbial deodorant. Therefore, it was better to spray microbial deodorant twice a week on Monday and Thursday to reduce the NH3, CO2, and N2O concentrations in rabbit houses. The NH3, CO2, N2O, and CH4 concentrations first showed a decreasing trend and then an increasing trend over 5 days in the summer and 7 days in the winter after VenaZn deodorant was sprayed in the rabbit house, and the NH3, CO2, N2O, and CH4 concentrations on day 3 and day 4 were significantly lower than they were on the other days.